Gut Microbiota-Derived Trimethylamine Promotes Inflammation with a Potential Impact on Epigenetic and Mitochondrial Homeostasis in Caco-2 Cells - Laura Bordoni; Irene Petracci; Giulia Feliziani; Gaia de Simone; Chiara Rucci; Rosita Gabbianelli (Antioxidants)
Trimethylamine (TMA), a byproduct of gut microbiota metabolism from dietary precursors, is not only the precursor of trimethylamine-N-oxide (TMAO) but may also affect gut health. An in vitro model of intestinal epithelium of Caco-2 cells was used to evaluate the impact of TMA on inflammation, paracellular permeability, epigenetics and mitochondrial functions. The expression levels of pro-inflammatory cytokines (IL-6, IL-1β) increased significantly after 24 h exposure to TMA 1 mM. TMA exposure was associated with an upregulation of SIRT1 (TMA 1 mM, 400 μM, 10 μM) and DNMT1 (TMA 1 mM, 400 µM) genes, while DNMT3A expression decreased (TMA 1 mM). In a cell-free model, TMA (from 0.1 µM to 1 mM) induced a dose-dependent reduction in Sirtuin enzyme activity. In Caco-2 cells, TMA reduced total ATP levels and significantly downregulated ND6 expression (TMA 1 mM). TMA excess (1 mM) reduced intracellular mitochondrial DNA copy numbers and increased the methylation of the light-strand promoter in the D-loop area of mtDNA. Also, TMA (1 mM, 400 µM, 10 µM) increased the permeability of Caco-2 epithelium, as evidenced by the reduced transepithelial electrical resistance values. Based on our preliminary results, TMA excess might promote inflammation in intestinal cells and disturb epigenetic and mitochondrial homeostasis.